Breakfast patterns among low-income, ethnically-diverse 4(th)-6(th) grade children in an urban area - Lawman, Hannah G (BioMed Central, 2014)
BACKGROUND: Increasing school breakfast participation has been advocated as a method to prevent childhood obesity. However, little is known about children’s breakfast patterns outside of school (e.g., home, corner store). Policies that increase school breakfast participation without an understanding of children’s breakfast habits outside of school may result in children consuming multiple breakfasts and may undermine efforts to prevent obesity. The aim of the current study was to describe morning food and drink consumption patterns among low-income, urban children and their associations with relative weight. METHODS: A cross-sectional analysis was conducted of data obtained from 651 4(th)-6(th) graders (51.7% female, 61.2% African American, 10.7 years) in 2012. Students completed surveys at school that included all foods eaten and their locations that morning. Height and weight were measured by trained research staff. RESULTS: On the day surveyed, 12.4% of youth reported not eating breakfast, 49.8% reported eating one breakfast, 25.5% reported eating two breakfasts, and 12.3% reported eating three or more breakfasts. The number of breakfasts consumed and BMI percentile showed a significant curvilinear relationship, with higher mean BMI percentiles observed among children who did not consume any breakfast and those who consumed ≥ 3 breakfasts. Sixth graders were significantly less likely to have consumed breakfast compared to younger children. A greater proportion of obese youth had no breakfast (18.0%) compared to healthy weight (10.1%) and overweight youth (10.7%, p = .01). CONCLUSIONS: When promoting school breakfast, policies will need to be mindful of both over- and under-consumption to effectively address childhood obesity and food insecurity. CLINICAL TRIAL REGISTRATION: NCT01924130 from http://clinicaltrials.gov/.